INTERDISCIPLINARY EDUCATION WITH ISLAMIC PRINCIPLES: NURTURING SUSTAINABLE MINDS FOR ISLAMIC EDUCATIONAL EXCELLENCE - Maspul, Kurniawan Arif (Rihlah Review: Jurnal Pendidikan Islam, 2023)
Confronting the widespread issue of bullying in Indonesian schools necessitates a thorough understanding of its underlying causes. A recent study emphasizes the importance of tackling this issue, with statistics demonstrating greater incidences of bullying among male Indonesian students in elementary school. This article investigates the use of Islamic ethics in education, notably in Indonesia, to combat bullying through interdisciplinary approaches. It envisions a comprehensive educational system based on Islamic ideals, focusing on administrative assistance, evaluation and assessment, community involvement, and teacher collaboration. This qualitative research provides significant insights for educators and policymakers who want to increase educational quality while sticking to Islamic ideals. Key components such as administrative support, evaluation and assessment, community involvement, and teacher collaboration are examined through the prism of Islamic values. This qualitative research provides valuable insights for educators and policymakers trying to improve educational quality while adhering to Islamic beliefs.